The fifth anniversary of the Mark Meerovich Prize: the sun, the duty and the heart - Lisitsina, Yana; Lisitsin, Vasily (project baikal, 2025)
The article examines the significance and course of the fifth anniversary award ceremony named after Mark Grigoryevich Meerovich (1956-2018), which took place in Irkutsk on October 4, 2025. The award is positioned as a key element in the system of public and professional support for researchers and practitioners involved in the preservation of the architectural and historical heritage of the region. Attention is paid to the launch and presentation of two badges – the honorary badge “Heart of Irkutsk” as an act of official recognition of the civic position and contribution of senior officials, and the badge of the Mark Meerovich Award as a distinction of the award winners. The ceremony demonstrates the effective integration of scientific and educational activities, community activism and public administration in the field of cultural heritage protection.